Immunohistochemical positive stained p53 protein in bladder transitional cell carcinoma - Halimi Monireh; Salehi Alireza; Baybordi Hosein; Nezami Nariman (Wolters Kluwer Medknow Publications, 2009)
Background: Molecular genetics and immunopathologic analysis of bladder cancer have shown some abnormalities in a number of genes and proteins that have been implicated in the development and progression of such tumors, mainly in the p53 pathway. Aims: To investigate the rate of positively stained p53 protein in patients with urothelial papillary carcinoma of the bladder (UCB) by immunohistochemistry and its relationship with tumor grade, gender and age of the patients. Settings and Design: During the present cross-sectional study, 100 paraffin-embedded specimens of UCB, which were provided from biopsies of the bladder by transurethral access, were immunohistochemically stained and studied for p53 protein from May 2006 to May 2007 in our referral center pathology laboratory. Materials and Methods: First, 4 µm slices of paraffin sections were provided and then stained by the avidin-biotin peroxidase method. The rate of positively stained p53 protein (defined as positive nuclear staining in over 10% of the cells) was assessed. This rate was also estimated and compared between grades, genders and age-related groups (< 70 years, ≥70 years). Statistical Analysis: The χ2 , Fisher′s exact test and Mann-Whitney U test were used for comparing. Results: The overall rate of positively stained specimens was 11% for nuclear p53 protein. This rate was significantly higher in females (10/29 vs. 1/71; P < 0.001; odds ratio [OR]: 0.23; 95% confidence interval [CI]: 4.43-306.08), patients with 70 or older than 70 years (8/42 vs. 3/58; P = 0.04; OR: 0.55; 95% CI: 1.07-17.39) and in high-grade tumors (10/58 vs. 1/42; P = 0.02; OR: 0.59; 95% CI: 0.01-0.95). Conclusions: The rate of positively stained p53 protein for UCB was lower in our population. This rate was also higher in females, patients with 70 or older than 70 years and high grade of UCB.